Self-efficacy and sports skill for elite Chinese female volleyball players - Zhai, H.; Feng, C. (2008 International Convention on Science, Education and Medicine in Sport: Proceedings, Vol. II, 2008)
Introduction Self-efficacy theory holds the idea that individuals` perception of their own ability and belief in the context of the incidents plays a decisive role in the control of behaviour regulation. This theory is the core of self-regulating system. The theory applies to competitive volleyball, which is a very competitive event with high achievements and stress. Thus self-efficacy is of great significance during players` training and competitions. This paper studied the relation between elite Chinese female volleyball players` self-efficacy and their sports skills. The findings will provide a corresponding theoretical reference for volleyball coaches` scientific psychological selection of talented players and for scientific psychological skills training. Methods A comprehensive review of the literature was undertaken. Interviews and questionnaires were conducted. After expert assessment and forecast this study used the players` self-efficacy survey questionnaire according to Bandura` principle of self-efficacy. Upon completion of the questionnaire, good validity was obtained. Using a Panasonic NV-GS70EN digital video seven games of 2007 "Bubugao" National Women's Volleyball Championship were recorded and analyzed. SPSS10.0 statistical software package was used for data analysis and statistical analysis. Results / Discussion Self-efficacy has a significant correlation with the game achievements. The players with good achievements have a high level of self-efficacy. Elite Chinese female volleyball players` self-efficacy have a linear correlation with their sports skills. Self-efficacy correlated with the first pass rate, followed by spiking scoring rate, from defense to attack rate, serve success rate and effective block rate. Relations between self-efficacy and sports skills for players in different positions show: the main attackers` self-efficacy hs a significant correlation with successful spiking deduction rate, a rate-in place, from defense to attack rate and the effective rate block. The assistant attackers` self-efficacy has a significant correlation with successful spiking deduction rate, a rate-related notable place; drugs and the self-efficacy-serve success rate, successful spiking deduction rate, a place - rate, from defense to attack. The passers` self-efficacy has a significant correlation with good rate, effective block rates; free man` self-efficacy has a significant correlation with the prevention of attack. Conclusions In regular training and competitions, coaches should arrange the training and competition according to the characteristics of each technique and the relative degree of self-efficacy, pay attention to the cultivation and improvement of self-efficacy, so that the full potential of players can be achieved.